Negative electrode sheet, method for manufacturing the same, battery, and electric device

CN120784265BActive Publication Date: 2026-10-27CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410405430.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-03
Publication Date
2026-10-27
Estimated Expiration
2044-04-03

AI Technical Summary

Technical Problem

[0003]传统的碱金属离子电池在充电过程中、尤其是在快速充电过程中,容易产生浓差极化,导致碱金属离子易在负极表面积累,即液相电势过大,从而导致析出碱金属并会产生碱金属枝晶

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120784265B_ABST
    Figure CN120784265B_ABST
Patent Text Reader

Abstract

The application relates to a negative electrode sheet, a preparation method thereof, a battery and an electric device. The negative electrode sheet comprises a current collector and a negative active layer arranged on at least one surface of the current collector, wherein the negative active layer comprises a negative active material and a molecular sieve; and the pore diameter D of the molecular sieve satisfies D<=10 nm. When the negative electrode sheet is used to prepare a battery, the fast-charging performance and the cycle stability of the battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery technology, and in particular to a negative electrode sheet and its preparation method, a battery, and an electrical device. Background Technology

[0002] Lithium-ion batteries and other alkali metal-ion batteries are increasingly widely used due to their clean and renewable characteristics, and have been widely applied in many fields such as consumer electronics, electric vehicles, and energy storage.

[0003] Traditional alkali metal ion batteries are prone to concentration polarization during charging, especially during fast charging. This leads to the accumulation of alkali metal ions on the negative electrode surface, resulting in excessive liquid phase potential. Consequently, alkali metals are deposited and alkali metal dendrites form. Taking lithium-ion batteries as an example, due to the excellent conductivity and low potential of lithium metal, lithium metal ions preferentially accumulate near lithium dendrites and are further reduced to form lithium dendrites. This process is accompanied by volume changes, which can easily cause the SEI film to rupture, resulting in the loss of active lithium. Furthermore, the continuously deposited elemental lithium can detach from the negative electrode surface, forming "dead lithium" that cannot participate in the reaction. This leads to a decrease in the energy density and cycle performance of the secondary battery. In severe cases, sharp morphologies can pierce the separator, causing a short circuit within the battery, potentially leading to catastrophic consequences such as combustion or explosion.

[0004] Therefore, traditional technologies still need further improvement. Summary of the Invention

[0005] Therefore, it is necessary to provide a negative electrode sheet and its preparation method, a battery and an electrical device, with the aim of improving the fast charging performance and cycle stability of the battery.

[0006] A first aspect of this application provides a negative electrode sheet, including a current collector and a negative electrode active layer disposed on at least one surface of the current collector, the negative electrode active layer including a negative electrode active material and a molecular sieve;

[0007] The pore size D of the molecular sieve satisfies: D≤10nm.

[0008] In the aforementioned negative electrode sheet, adding a molecular sieve to the negative electrode active layer, with its abundant nanopores and numerous charge-rich centers, allows for the following effects when applied to battery fabrication, taking alkali metal ion batteries as an example, by controlling its specific pore size range: The molecular sieve with its specific pore size can electrostatically attract solvated alkali metal ions on the surface of the negative electrode active layer. That is, the specific pore size of the molecular sieve nanoconfines the solvated alkali metal ions, causing them to lose some solvent molecules, reducing the coordination number of solvent molecules or decreasing the interaction force with solvent molecules. This is equivalent to lowering the desolvation energy barrier at the negative electrode active layer interface, improving the transport of alkali metal ions within the negative electrode active layer. Furthermore, the partially desolvated lithium ions, due to the reduction in the organic solvent molecules surrounding them, decrease the organic component in the solid electrolyte interphase (SEI) produced by reduction decomposition, effectively increasing the proportion of inorganic components and thus increasing the diffusion rate of lithium ions in the SEI film. Therefore, the aforementioned negative electrode sheet can reduce the probability of metal dendrite formation, improving the battery's fast-charging performance and cycle stability.

[0009] Furthermore, the porous structure of molecular sieves facilitates the wetting of the negative electrode by the electrolyte, thereby improving the negative electrode's liquid retention capacity and lithium conduction capacity.

[0010] In some of these embodiments, 0.3nm ≤ D ≤ 10nm.

[0011] In some of these embodiments, 0.3nm ≤ D ≤ 1nm.

[0012] Further control of the molecular sieve pore size can enhance its promoting effect on the desolvation process.

[0013] In some embodiments, the molecular sieve includes at least one of silica-alumina molecular sieve, phosphorus-alumina molecular sieve, and silica-phosphorus-alumina molecular sieve.

[0014] In some embodiments, the molecular sieve includes aluminosilicate molecular sieves, which include at least one of the compounds of formula (1) and hydrates of the compounds of formula (1);

[0015] zQ·Al2O3·xSiO2 (1); Q includes M + 2O and M 2+ At least one of O;

[0016] Among them, M + Including H + Li + K + Na + At least one of them, M 2+ Including Ca 2+ Ba 2+At least one of the following; 0≤z≤1,0 <x≤2000。

[0017] In some of these embodiments, 20 ≤ x ≤ 1700.

[0018] In some of these embodiments, 100 ≤ x ≤ 500.

[0019] Further regulation of x essentially involves regulating the molar ratio of silicon to aluminum atoms in the molecular sieve, thereby increasing the number of negatively charged centers and further enhancing its promoting effect on the desolvation process.

[0020] In some embodiments, the silica-alumina molecular sieve includes at least one of potassium A-type molecular sieve, sodium A-type molecular sieve, calcium A-type molecular sieve, calcium Z-type molecular sieve, sodium Z-type molecular sieve, sodium Y-type molecular sieve, sodium mordenite zeolite molecular sieve, ZSM-5 molecular sieve, and TS-1 molecular sieve.

[0021] In some embodiments, the average particle size Dv50 of the molecular sieve satisfies: 0.1 μm. <Dv50≤20μm。

[0022] In some of these embodiments, 0.3 μm ≤ Dv50 ≤ 13 μm.

[0023] In some of these embodiments, 1μm≤Dv50≤3μm.

[0024] Research has found that, on the one hand, the smaller the particle size of the molecular sieve, the larger the contact surface with the negative electrode active material, which is more conducive to the embedding of active ions into the negative electrode material after combining with electrons; on the other hand, if the particle size of the molecular sieve is too small, it is more prone to agglomeration, making dispersion difficult, and the raw material production is more difficult and costly. Therefore, further controlling the particle size Dv50 of the molecular sieve can further improve the cycle stability of the battery.

[0025] In some embodiments, the specific surface area S of the molecular sieve satisfies: 0 <S≤1500m 2 / g.

[0026] In some embodiments, the specific surface area S of the molecular sieve satisfies: 200 m² / s². 2 / g≤S≤500m 2 / g.

[0027] In some embodiments, the mass ratio of the molecular sieve to the negative electrode active material in the negative electrode active layer is (0.001~0.1):1.

[0028] In some embodiments, the mass ratio of the molecular sieve to the negative electrode active material in the negative electrode active layer is (0.005~0.03):1.

[0029] In some embodiments, the molecular sieve and the negative electrode active material are mixed together in the negative electrode active layer.

[0030] A second aspect of this application provides a method for preparing a negative electrode sheet, comprising the following steps:

[0031] A negative electrode active layer is formed on at least one side of the current collector using a negative electrode active slurry; the negative electrode active slurry includes a negative electrode active material and a molecular sieve, wherein the pore size D of the molecular sieve satisfies: D≤10nm.

[0032] In some embodiments, the preparation steps of the negative electrode active slurry include the following steps:

[0033] The negative electrode active material, the molecular sieve, and the solvent are mixed.

[0034] A third aspect of this application provides a battery comprising a negative electrode sheet prepared by the method of the first aspect or the second aspect.

[0035] A fourth aspect of this application provides an electrical device comprising the battery of the third aspect. Attached Figure Description

[0036] Various other advantages and benefits will become apparent to those skilled in the art upon reading the detailed description of the preferred embodiments below. The accompanying drawings are for illustrative purposes only and are not intended to limit the scope of this application. Furthermore, the same reference numerals denote the same parts throughout the drawings. In the drawings:

[0037] Figure 1 This is a schematic diagram illustrating the solvation and desolvation processes of lithium ions during the charging and discharging of a traditional lithium-ion battery.

[0038] Figure 2 This is a schematic diagram illustrating the solvation and desolvation process of lithium ions during charging and discharging of a lithium-ion battery prepared from the negative electrode sheet of this application.

[0039] Figure 3 This is a schematic diagram showing the mixed state of molecular sieve and negative electrode active material in the negative electrode active layer of the negative electrode sheet of this application.

[0040] Figure 4 This is a schematic diagram of one embodiment of a battery cell;

[0041] Figure 5 yes Figure 4 Exploded view;

[0042] Figure 6 This is a schematic diagram of one embodiment of the battery pack;

[0043] Figure 7 yes Figure 6 Exploded view;

[0044] Figure 8 This is a schematic diagram of one embodiment of an electrical device in which a battery is used as a power source;

[0045] Figure 9 This is a comparison chart of the charging curves of the batteries prepared in Example 1 and Comparative Example 1; where (a) is the charging curve of the battery prepared in Example 1 and (b) is the charging curve of the battery prepared in Comparative Example 1.

[0046] Figure 10 These are comparison diagrams of the electrochemical impedance spectra of the batteries prepared in Example 1 and Comparative Example 1, where (a) is the electrochemical impedance spectrum of the battery prepared in Example 1 and (b) is the electrochemical impedance spectrum of the battery prepared in Comparative Example 1.

[0047] Figure 11 These are physical images of the negative electrode sheets separated after cyclic charging and discharging of the batteries prepared in Example 1 and Comparative Example 1, where (a) is a physical image of the negative electrode sheet of Example 1 and (b) is a physical image of the negative electrode sheet of Comparative Example 1.

[0048] Explanation of reference numerals in the attached figures:

[0049] 1. Battery pack; 2. Upper casing; 3. Lower casing; 4. Individual battery cell; 41. Housing; 42. Electrode assembly; 43. Cover plate; 5. Electrical device. Detailed Implementation

[0050] To make the above-mentioned objectives, features, and advantages of this application more apparent and understandable, a detailed description of specific embodiments of this application is provided below. Many specific details are set forth in the following description to provide a thorough understanding of this application. However, this application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar modifications without departing from the spirit of this application. Therefore, this application is not limited to the specific embodiments disclosed below.

[0051] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of that feature. In the description of this application, "multiple" means at least two, such as two, three, etc., unless otherwise explicitly specified.

[0052] In traditional technologies, secondary batteries are prone to producing elemental metals during charging and discharging, especially during fast charging. For example, lithium-ion batteries are prone to producing dead lithium, such as lithium metal dendrites, which reduces the cycle stability of the battery. Traditional technologies often suppress the formation of lithium dendrites by optimizing the electrolyte composition or improving the active materials, but the suppression effect is limited.

[0053] Research has found that during battery charging, the transport of metals between the positive and negative electrodes mainly relies on the solvent in the electrolyte. Taking alkali metal ion batteries as an example, during the transport process, alkali metal ions undergo solvation and desolvation: During charging, alkali metal ions diffuse from the lattice on the positive electrode side into the electrolyte. The alkali metal ions attract solvent molecules to gather around them through forces such as coordination bonds, hydrogen bonds, or dipole interactions, which is equivalent to forming "wings," called "solvation." This accelerates the diffusion of alkali metal ions in the solution, and the solvation structure of alkali metal ions affects the SEI structure and composition formed during formation. When they reach the SEI position on the negative electrode surface, because the "wings" of the solvated alkali metal ions are too large, the resistance to transporting them into the negative electrode active layer through the pores of the SEI is too great, so they have to remove the solvent molecules adsorbed on the surface. This process is called desolvation. Then, after passing through the SEI, they combine with electrons and embed themselves into the negative electrode material, completing the charging process.

[0054] Further research revealed that the desolvation process is a decomposition coordination process with a certain energy barrier (the kinetic energy barrier is as high as 50~70kJ / mol). Its difficulty is related to the magnitude of the interaction forces formed during solvation, which is specifically related to the type of solvent molecules, additives, concentration, and metal salts in the electrolyte. If the desolvation process is too difficult, it will lead to the accumulation of some alkali metal ions, resulting in polarization and the formation of alkali metal dendrites, which will lead to a decrease in battery performance.

[0055] Based on this, the technical solution of this application was obtained after a large number of experimental studies.

[0056] One embodiment of this application provides a negative electrode sheet, including a current collector and a negative electrode active layer disposed on at least one surface of the current collector, the negative electrode active layer including a negative electrode active material and a molecular sieve.

[0057] The pore size D of the molecular sieve satisfies: D≤10nm.

[0058] In the aforementioned negative electrode sheet, a molecular sieve is added to the negative electrode active layer. This molecular sieve possesses abundant nanopores and negatively charged centers. By controlling its specific pore size range, taking an alkali metal ion battery as an example, the following effects can be achieved: The molecular sieve with its specific pore size exerts an electrostatic attraction on the solvated alkali metal ions on the surface of the negative electrode active layer. That is, the specific pore size of the molecular sieve nano-confines the solvated alkali metal ions, causing them to lose some solvent molecules, reducing the coordination number of solvent molecules or decreasing the interaction force with solvent molecules. This is equivalent to lowering the desolvation energy barrier at the interface of the negative electrode active layer, thus improving the transport of alkali metal ions in the negative electrode active layer. Furthermore, the partially desolvated alkali metal, due to the reduction in the organic solvent molecules surrounding it, reduces the organic component in the solid electrolyte interphase (SEI) film generated by reduction decomposition, effectively increasing the proportion of inorganic components and thereby increasing the diffusion rate of lithium ions in the SEI film. Therefore, the aforementioned negative electrode sheet can reduce the probability of alkali metal dendrite formation, improving the battery's fast-charging performance and cycle stability.

[0059] The following uses a lithium-ion battery system as an example to illustrate the solvation and desolvation processes during charging and discharging. The electrolyte contains ethylene carbonate (EC). Please refer to [reference needed] for details. Figure 1 and Figure 2 .

[0060] Figure 1 This diagram illustrates the solvation and desolvation processes of lithium ions during charging and discharging in a traditional lithium-ion battery. During charging, lithium ions diffuse from the lattice on the positive electrode side into the electrolyte. The lithium ions attract solvent molecules in the electrolyte, such as ethylene carbonate (EC), through coordination bonds, forming highly coordinated compounds like Li(EC)₄, which are essentially "wings"—a process known as "solvation." When they reach the SEI (Sediment Ion) site on the negative electrode surface, the solvated metal ions' "wings" are too large, creating significant resistance to transmission through the SEI pores into the negative electrode active layer. Only a portion can detach from the adsorbed solvent molecules on the surface; this process is called desolvation. After passing through the SEI film, they recombine with electrons and embed into the negative electrode material, completing the charging process. A higher coordination number, equivalent to more "wings" around the lithium ion, results in a higher energy barrier for desolvation.

[0061] Please refer to further details. Figure 2 , Figure 2 A schematic diagram illustrating the solvation and desolvation processes of lithium ions during charging and discharging in a lithium-ion battery prepared using the negative electrode of this application. The solvation of lithium ions is related to the process described above. Figure 1The process is the same. When the molecular sieve in the active layer of the negative electrode reaches the SEI position, it uses its nanopores to confine the solvated alkali metal ions in a nanoscale manner, causing the solvated lithium alkali metal ions to remove some solvent molecules (i.e., sieve desolvation) and reduce the coordination number of the solvent molecules (e.g., Li(EC)). n (n < 4) is equivalent to lowering the desolvation energy barrier at the interface of the negative electrode active layer, reducing the transport resistance of alkali metal ions in the negative electrode active layer, thereby improving the fast charging performance and cycle stability of the battery.

[0062] In some of these embodiments, 0.3nm ≤ D ≤ 10nm.

[0063] In some of these embodiments, 0.3nm ≤ D ≤ 1nm.

[0064] Further control of the molecular sieve pore size can enhance its promoting effect on the desolvation process.

[0065] In the above "0.3nm ≤ D ≤ 10nm", the specific values ​​of D include the minimum and maximum values ​​within this range, as well as every value between the minimum and maximum values. Specific examples include, but are not limited to, the point values ​​in the embodiments and the following point values: 0.3nm, 0.4nm, 0.5nm, 0.6nm, 0.7nm, 0.8nm, 0.9nm, 1nm, 1.1nm, 1.2nm, 1.3nm, 1.4nm, 1.5nm, 1.6nm, 1.7nm. nm, 1.8nm, 1.9nm, 2nm, 2.1nm, 2.2nm, 2.3nm, 2.4nm, 2.5nm, 2.6nm, 2.7nm, 2.8nm, 2.9nm, 3nm, 3.1nm, 3.2nm, 3.3nm, 3.4nm, 3.5nm, 3.6nm, 3.7nm, 3.8nm, 3.9nm, 4nm, 4.1nm, 4.2nm, 4.3nm, 4.4nm, 4.5nm, 4 .6nm, 4.7nm, 4.8nm, 4.9nm, 5nm, 5.1nm, 5.2nm, 5.3nm, 5.4nm, 5.5nm, 5.6nm, 5.7nm, 5.8nm, 5.9nm, 6 nm, 6.1nm, 6.2nm, 6.3nm, 6.4nm, 6.5nm, 6.6nm, 6.7nm, 6.8nm, 6.9nm, 7nm, 7.1nm, 7.2nm, 7.3nm, 7.4n The range of wavelengths is 10nm, 7.5nm, 7.6nm, 7.7nm, 7.8nm, 7.9nm, 8nm, 8.1nm, 8.2nm, 8.3nm, 8.4nm, 8.5nm, 8.6nm, 8.7nm, 8.8nm, 8.9nm, 9nm, 9.1nm, 9.2nm, 9.3nm, 9.4nm, 9.5nm, 9.6nm, 9.7nm, 9.8nm, 9.9nm, or 10nm; or any range of two values.

[0066] In some embodiments, the molecular sieve includes at least one of silica-alumina molecular sieve, phosphorus-alumina molecular sieve, and silica-phosphorus-alumina molecular sieve.

[0067] In some embodiments, the molecular sieve includes aluminosilicate molecular sieves, which include at least one of the compounds of formula (1) and hydrates of the compounds of formula (1):

[0068] zQ·Al2O3·xSiO2(1); Q is selected from M + 2O and M 2+ At least one of O;

[0069] Among them, M + Including H + Li + K + Na+ at least one of, M 2+ includes Ca 2+ , Ba 2+ at least one of; 0≤z≤1, 0<x≤2000.

[0070] The hydrate of the compound represented by formula (1) is formed after the compound represented by formula (1) absorbs water, and its specific molecular formula can be expressed as: zQ·Al₂O₃·xSiO₂·yH₂O, where the meanings of z and x are the same as above. Since silicon-aluminum molecular sieves have excellent water absorption, in the art, y can take any value greater than 0, which will not be elaborated here.

[0071] In some of the embodiments, Q includes M + ₂O, M + includes Li + or Na + . Further, M can be preferably selected according to the battery system of specific application + , for example, for a lithium-ion battery, M + is selected from Li + , and for a sodium-ion battery, M + is selected from Na + .

[0072] It can be understood that the value of x mentioned above can characterize the molar ratio of SiO₂ to Al₂O₃ in the silicon-aluminum molecular sieve.

[0073] In some of the embodiments, 20≤x≤1700.

[0074] In some of the embodiments, 100≤x≤500.

[0075] Further adjusting x is essentially regulating the molar ratio of SiO₂ to Al₂O₃ (also known as the silica-alumina ratio) of the molecular sieve, so that the molecular sieve contains more negative charge centers, which further improves the promoting effect on the desolvation process. In the above "0<x≤2000", the specific values of x include the minimum value and the maximum value of this range, and every value between the minimum value and the maximum value. Specific examples include but are not limited to the point values in the embodiments and the following point values: 10, 30, 50, 100, 150, 200, 250, 300, 350, 400, 450, 500, 550, 600, 650, 700, 750, 800, 850, 900, 950, 1000, 1100, 1200, 1300, 1400, 1500, 1600, 1700, 1800, 1900, 2000; or a range composed of any two numerical values.

[0076] In some embodiments, the silica-alumina molecular sieve includes at least one of potassium A-type molecular sieve, sodium A-type molecular sieve, calcium A-type molecular sieve, calcium Z-type molecular sieve, sodium Z-type molecular sieve, sodium Y-type molecular sieve, sodium mordenite zeolite molecular sieve, ZSM-5 molecular sieve, and TS-1 molecular sieve.

[0077] Specifically, silica-alumina molecular sieves include at least one of the following: 3A molecular sieve (potassium A type), 4A molecular sieve (sodium A type), 5A molecular sieve (calcium A type), 10Z molecular sieve (calcium Z type), 13Z molecular sieve (sodium Z type), Y-type molecular sieve (sodium Y type), sodium mordenite zeolite type, ZSM-5 and TS-1 type molecular sieves.

[0078] It should be noted that the pore size of a molecular sieve refers to the pore size mainly determined by its crystal framework and elements, which together form the channels. Molecular sieves are primarily classified into type A, type X, type Y, and type Z based on their crystal structure. The number before the model number represents the pore size; for example, the effective pore size of 4A molecular sieve (sodium type A) is 0.4 nm. 2+ Exchange Na in 4A molecular sieve + This results in a pore size of 5A, which is called 5A molecular sieve (also known as calcium A type) molecular sieve; using K + Exchange Na of 4A molecular sieve + This forms a pore size of 3A, which is called 3A (also known as potassium A type) molecular sieve.

[0079] In some embodiments, the average particle size Dv50 of the molecular sieve satisfies: 0.1 μm. <Dv50≤20μm。

[0080] In some of these embodiments, 0.3 μm ≤ Dv50 ≤ 13 μm.

[0081] In some of these embodiments, 1μm≤Dv50≤3μm.

[0082] Research has found that, on the one hand, the smaller the particle size of the molecular sieve, the larger the contact surface with the negative electrode active material, which is more conducive to the embedding of active metal ions into the negative electrode material after combining with electrons; on the other hand, if the particle size of the molecular sieve is too small, it is more prone to agglomeration, making dispersion difficult, and the raw material production is more difficult and costly. Therefore, further controlling the particle size Dv50 of the molecular sieve can further improve the cycle stability of the battery.

[0083] It can be understood that the above-mentioned average particle size Dv50 refers to the volume average particle size, that is, the particle sizes corresponding to 50% and 5% of the cumulative volume distribution percentage of the material, which can be measured by instruments and methods known in the art. For example, it can be conveniently measured using a laser particle size analyzer with reference to GB / T 19077-2016 Particle Size Distribution - Laser Diffraction Method. The test instrument may be the Mastersizer 2000E laser particle size analyzer from Malvern Instruments Limited, UK.

[0084] In the above "0.1μm < Dv50 ≤ 20μm", the specific values of Dv50 include the minimum and maximum values of this range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the examples and the following point values: 0.1μm, 0.15μm, 0.2μm, 0.25μm, 0.3μm, 0.35μm, 0.4μm, 0.45μm, 0.5μm, 0.55μm, 0.6μm, 0.65μm, 0.7μm, 0.75μm, 0.8μm, 0.85μm, 0.9μm, 0.95μm, 1μm, 1.1μm, 1.2μm, 1.3μm, 1.4μm, 1.5μm, 1.6μm, 1.7μm, 1.8μm, 1.9μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm, 20μm; or a range composed of any two numerical values.

[0085] In some of the embodiments, the specific surface area S of the molecular sieve satisfies: 0 < S ≤ 1500m 2 / g.

[0086] In some of the embodiments, the specific surface area S of the molecular sieve satisfies: 200m 2 / g < S ≤ 500m 2 / g.

[0087] In the above "0 < S ≤ 1500m 2 / g", the specific values of S include the minimum and maximum values of this range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the examples and the following point values: 100m 2 / g, 150 m 2 / g, 200 m 2 / g, 250 m 2 / g, 300 m 2 / g, 350 m 2 / g, 400 m 2 / g, 450 m 2 / g、500 m 2 / g、550m 2 / g、600 m 2 / g、650 m 2 / g、700 m 2 / g、750 m 2 / g、800 m 2 / g、850 m 2 / g、900 m 2 / g、950 m 2 / g, 1000 m 2 / g、1100 m 2 / g、1200 m 2 / g、1300 m 2 / g、1400 m 2 / g, 1500 m 2 / g; or a range consisting of any two values.

[0088] In some embodiments, the mass ratio of molecular sieve to negative electrode active material in the negative electrode active layer is (0.001~0.1):1.

[0089] In some embodiments, the mass ratio of molecular sieve to negative electrode active material in the negative electrode active layer is (0.005~0.03):1.

[0090] In some embodiments, the mass percentage of the negative electrode active material in the negative electrode active layer is 90% to 99%.

[0091] In some embodiments, the molecular sieve and the negative electrode active material are mixed together in the negative electrode active layer.

[0092] The aforementioned "mutual mixing" means that the molecular sieve and the negative electrode active material do not need to have a specific distribution pattern in the negative electrode active layer. They are physically mixed, with a portion of the negative electrode active material's surface in direct contact with the molecular sieve; this can be considered as the molecular sieve being dispersed within the negative electrode active material. Please refer to [link / reference] for details. Figure 3 , Figure 3 This is a schematic diagram showing the mixed state of molecular sieve and negative electrode active material in the negative electrode active layer of the negative electrode sheet provided in one embodiment of this application.

[0093] The aforementioned negative electrode active material can be any commonly used negative electrode active material described in this application.

[0094] In any embodiment of this application, the aforementioned negative electrode active material includes at least one of the following: mesophase carbon microspheres, graphite, glassy carbon, carbon nanotubes, carbon-carbon composite materials, carbon fibers, hard carbon, soft carbon, silicon-based materials, tin-based materials, magnesium-based materials, or iron-based materials.

[0095] Optionally, specific examples of the above-mentioned negative electrode active materials include, but are not limited to, at least one of the following: mesophase carbon microspheres, natural graphite, artificial graphite, graphene, glassy carbon, carbon nanotubes, carbon fibers, hard carbon, soft carbon, iron oxide, tin oxide, silicon oxide, magnesium oxide, silicon-carbon composites, lithium metal, or lithium metal alloys.

[0096] In some embodiments, the average particle size Dv50 of the negative electrode active material is 0.5 μm to 50 μm. Specific values ​​for Dv50 include the minimum and maximum values ​​within this range, as well as every value between these values. Specific examples include, but are not limited to, the point values ​​in the embodiments and the following point values: 0.5 μm, 0.55 μm, 0.6 μm, 0.65 μm, 0.7 μm, 0.75 μm, 0.8 μm, 0.85 μm, 0.9 μm, 0.95 μm, 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm, 2 μm. 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm, 20μm, 25μm, 30μm, 35μm, 40μm, 45μm, 50μm; or any range of two values.

[0097] In some embodiments, the average particle size Dv50 of the negative electrode active material is greater than the average particle size Dv50 of the molecular sieve.

[0098] In some embodiments, the negative electrode active layer also includes a conductive agent.

[0099] In some embodiments, the conductive agent accounts for 0.1% to 1% of the mass of the negative electrode active layer.

[0100] In any embodiment of this application, the conductive agent described above may be a commonly used conductive agent in the art, including but not limited to at least one of graphite, carbon nanotubes, nanofibers, carbon black, or graphene. Specifically, it may be selected from at least one of SP, KS-6, acetylene black, branched Ketjen black ECP, SFG-6, vapor-grown carbon fiber VGCF, carbon nanotubes CNTs, and graphene or composite conductive agents thereof.

[0101] In some embodiments, the negative electrode active layer further includes a binder.

[0102] In any embodiment of this application, the adhesive can be a commonly used adhesive in the art, selected from at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-tetrafluoroethylene-propylene terpolymer, ethylene-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, hydrogenated nitrile rubber, styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), carboxymethyl chitosan (CMCS), and fluorinated acrylate resins.

[0103] Furthermore, it can be understood that the current collector has two surfaces arranged opposite to each other in its own thickness direction, and a negative electrode active layer is provided on at least one surface. It can be one of the surfaces or both surfaces can be provided with a negative electrode active layer.

[0104] In some embodiments, the current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be formed by forming a metal material on a polymer substrate.

[0105] In some embodiments, the metallic material includes at least one selected from aluminum, aluminum alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys.

[0106] In some embodiments, the polymer material substrate includes at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).

[0107] According to one embodiment of this application, a method for preparing a negative electrode sheet is also provided, including the following step S10.

[0108] Step S10: A negative electrode active layer is formed on at least one side of the current collector using a negative electrode active slurry; the negative electrode active slurry includes a negative electrode active material and a molecular sieve, and the pore size D of the molecular sieve satisfies: D≤10nm.

[0109] The selection and addition amount of molecular sieves and negative electrode active materials are as described above and will not be repeated here.

[0110] In some embodiments, the preparation steps of the negative electrode active slurry include the following steps:

[0111] The negative electrode active material, molecular sieve, and solvent are mixed.

[0112] Furthermore, the above mixing steps are carried out under stirring conditions.

[0113] In some embodiments, the negative electrode active slurry includes a solvent; further, the solid content of the negative electrode active slurry is 40wt%~80wt%, and the viscosity at 25°C is adjusted to 5000mPa·s~25000mPa·s.

[0114] In some embodiments, the solvent includes, but is not limited to, water.

[0115] According to one embodiment of this application, a battery is also provided, which includes the above-described negative electrode sheet or a negative electrode sheet prepared by the above-described negative electrode sheet preparation method.

[0116] In some embodiments, the battery includes an alkali metal ion battery; including but not limited to at least one of lithium-ion batteries, sodium-ion batteries, and potassium-ion batteries.

[0117] Furthermore, the aforementioned battery includes a positive electrode and a separator, and the negative electrode, separator, and positive electrode can be wound together to form a battery assembly.

[0118] The separator and positive electrode can be any type of alkali metal ion battery applicable to various alkali metal ion batteries in the art. The separator and positive electrode are described herein in a non-limiting manner, but are not limited to the following systems.

[0119] Positive electrode sheet: includes a current collector and a positive electrode active layer disposed on at least one surface of the current collector, the positive electrode active layer including a positive electrode material.

[0120] The positive electrode active material can be any commonly used positive electrode active material in the field, including but not limited to: positive electrode active materials for lithium-ion batteries, positive electrode active materials for sodium-ion batteries, and positive electrode active materials for potassium-ion batteries.

[0121] The positive electrode active materials for lithium-ion batteries, sodium-ion batteries, and potassium-ion batteries are referred to as lithium-ion active materials, sodium-ion active materials, or potassium-ion active materials, respectively, below.

[0122] Further, as an example, lithium-ion active materials may include at least one of the following materials: lithium phosphates with an olivine structure, lithium transition metal oxides, and their respective modified compounds. However, this application is not limited to these materials, and other conventional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Examples of lithium transition metal oxides may include, but are not limited to: lithium cobalt oxides (such as LiCoO2), lithium nickel oxides (such as LiNiO2), lithium manganese oxides (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxides, lithium manganese cobalt oxides, lithium nickel manganese oxides, and lithium nickel cobalt manganese oxides (such as LiNi). 1 / 3 Co 1 / 3 Mn 1 / 3O2 (also known as NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2 (also known as NCM523), LiNi 0.5 Co 0.25 Mn 0.25 O2 (also known as NCM211), LiNi 0.6 Co 0.2 Mn 0.2 O2 (also known as NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2 (abbreviated as NCM811), lithium nickel cobalt aluminum oxide (such as LiNi) 0.8 Co 0.15 Al 0.05 At least one of O2 or its modified compounds. Examples of lithium-containing phosphates with an olivine structure include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4, abbreviated as LFP), lithium manganese phosphate (such as LiMnPO4), or lithium manganese iron phosphate. In any embodiment of this application, the molecular formula of the lithium-ion active material is: LiFe x Mn (1-x) PO4, where x takes any number from 0 to 1.

[0123] It is understandable that when x is 0, LiFe x Mn (1-x) PO4 is LiMnPO4, which is lithium manganese phosphate. When x is 1, LiFe x Mn (1-x) PO4 is LiFePO4, which stands for lithium iron phosphate (LFP).

[0124] It should be noted that the lithium content in the cathode material mentioned above refers to its content when it is not in use. During battery use, it will be repeatedly charged, and the Li in the cathode active material will change during the charging and discharging process. That is, the molar subscript of Li in the cathode active material of the battery product will not always remain at 1, but will change; further, the range of change can be (0~1.2).

[0125] For example, LiFe x Mn (1-x) PO4 can be further represented as Li y Fe x Mn (1-x) PO4, y is 0~1.1.

[0126] For example, regarding the ternary material Li y (Ni a Co b Mnc ) 1-d M d O 2-x A x y is 0.2~1.2, a+b+c=1, 0≤d≤1, 0≤x<2; M is one or more of Zr, Sr, B, Ti, Mg, Sn or Al, and A is one or more of S, N, F, Cl, Br or I.

[0127] During the charging and discharging process, Li will be extracted and consumed. The molar content of Li will be different when the battery is discharged to different states. The above limitation on y includes the molar content of Li in different charging and discharging states of the battery. Furthermore, the battery voltage is usually between 2-5V.

[0128] In some embodiments, the active material includes a high-voltage positive electrode active material; further, the active material includes a nickel-containing active material; for example, it may be at least one of nickel-containing ternary materials, lithium nickel cobalt oxide, lithium nickel manganese oxide, or lithium nickel cobalt manganese oxide; more specifically, it may be at least one of lithium nickel manganese cobalt oxide, nickel manganese spinel, or lithium nickel-rich manganese oxide.

[0129] As an example, sodium-ion active materials may include at least one of the following: sodium transition metal oxides, polyanionic compounds, or Prussian blue compounds. However, this application is not limited to these materials, and other conventionally known materials that can be used as positive electrode active materials for sodium-ion batteries may also be used.

[0130] As an optional technical solution in this application, the transition metal in the sodium transition metal oxide includes at least one selected from Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr, or Ce. For example, the sodium transition metal oxide is Na. x MO2, wherein M includes at least one or more of Ti, V, Mn, Co, Ni, Fe, Cr or Cu, and 0 < x ≤ 1.

[0131] As an optional technical solution in this application, the polyanionic compound can be a compound containing sodium ions, transition metal ions, or a tetrahedral (YO4) structure. n- A class of compounds with anionic units. The transition metal includes at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr, or Ce; Y includes at least one of P, S, or Si; n represents (YO4). n- The price state.

[0132] Polyanionic compounds can also contain sodium ions, transition metal ions, or tetrahedral (YO4) ions. n-A class of compounds comprising anionic units and halide anions. Transition metals include at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr, or Ce; Y includes at least one of P, S, or Si, where n represents (YO4). n- The valence state; the halogen can be at least one of F, Cl or Br.

[0133] Polyanionic compounds can also be sodium-containing tetrahedral (YO4) compounds. n- Anionic unit, polyhedral unit (ZO) y ) m+ And a class of compounds with optional halide anions. Y includes at least one of P, S, or Si, and n represents (YO4). n- The valence state; Z represents a transition metal, including at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr, or Ce, and m represents (ZO). y ) m+ The valence state; the halogen can be at least one of F, Cl or Br.

[0134] Polyanionic compounds include, for example, NaFePO4, Na3V2(PO4)3 (sodium vanadium phosphate, abbreviated as NVP), Na4Fe3(PO4)2(P2O7) (NFPP), NaM1PO4F, or Na3(VO y )2(PO4)2F (3-2y) At least one of them.

[0135] M1 is at least one of V, Fe, Mn or Ni, and 0 ≤ y ≤ 1.

[0136] Prussian blue compounds can contain sodium ions, transition metal ions, and cyanide ions (CN). - A class of compounds. Transition metals include at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr, or Ce. Prussian blue compounds are, for example, Na. a M2 b M3 c (CN)6, wherein M2 and M3 are each independently selected from at least one of Ni, Cu, Fe, Mn, Co or Zn, 0 < a ≤ 2, 0 < b < 1, 0 < c < 1.

[0137] In any embodiment of this application, the current collector may be a metal foil or a composite current collector. For example, the positive electrode may be made of aluminum foil as the metal foil.

[0138] Composite current collectors may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. Composite current collectors can be formed by forming a metal material on a polymer substrate.

[0139] In some embodiments, the metallic material is selected from any one of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, or silver alloy.

[0140] In some embodiments, the polymer material substrate includes at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), or polyethylene (PE).

[0141] It is understood that the current collector has two surfaces arranged opposite each other in its own thickness direction, and a positive electrode active layer is sequentially provided on at least one surface. It can be one of the surfaces or both surfaces can be provided with a positive electrode active layer at the same time.

[0142] In some embodiments, the battery further includes an electrolyte, which is illustrated below, including but not limited to the following.

[0143] Separator: The separator is located between the positive electrode and the negative electrode.

[0144] The type of diaphragm used in this application can be any known porous diaphragm with good chemical and mechanical stability.

[0145] In some embodiments, the diaphragm material can be selected from at least one of glass fiber, nonwoven fabric, polyethylene, polypropylene, or polyvinylidene fluoride. The diaphragm can be a single-layer film or a multi-layer composite film. When the diaphragm is a multi-layer composite film, the materials of each layer can be the same or different.

[0146] The thickness of the diaphragm is controlled between 2 μm and 15 μm; optionally, the thickness of the diaphragm is controlled between 2 μm and 13 μm.

[0147] Generally, electrolytes include electrolyte salts and solvents.

[0148] In some embodiments, the electrolyte salt may be selected from electrolyte salts commonly used in the art, such as lithium-ion electrolyte salts.

[0149] As an example, lithium-ion electrolyte salts include, but are not limited to, one or more of the following: lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalate borate (LiDFOB), lithium dioxalate borate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorodioxalate phosphate (LiDFOP), or lithium tetrafluorooxalate phosphate (LiTFOP).

[0150] In some embodiments, the solvent may be selected from one or more of fluoroethylene carbonate (FEC), ethylene carbonate (EC), propylene carbonate (PC), methyl ethyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butyl carbonate (BC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS), or diethyl sulfone (ESE).

[0151] In some implementations, the concentration of the electrolyte salt in the electrolyte is typically 0.5 mol / L to 15 mol / L.

[0152] This application does not impose any particular limitation on the shape of the battery; the battery shape can be cylindrical, square, or any other arbitrary shape. For example, Figure 4 This is a sample of a square-structured battery cell 4.

[0153] In some embodiments, refer to Figure 5 The outer casing may include a housing 41 and a cover plate 43. The housing 41 may include a base plate and side plates connected to the base plate, the base plate and side plates forming a receiving cavity. The housing 41 has an opening communicating with the receiving cavity, and the cover plate 43 can be placed over the opening to close the receiving cavity.

[0154] The positive electrode, separator, and negative electrode can be formed into electrode assembly 42 by winding or stacking processes, and the electrode assembly 42 is encapsulated in a receiving cavity. The number of electrode assemblies 42 contained in a single battery cell 4 can be one or more, and can be adjusted according to requirements.

[0155] The battery comprises one or more battery cells 4.

[0156] The battery can be a battery module or a battery pack; a battery module or battery pack includes at least one battery cell 4. The number of battery cells contained in a battery module can be one or more, and those skilled in the art can select an appropriate number according to the application and capacity of the battery module.

[0157] Figure 6 and Figure 7 Here is an example of a battery pack 1. The battery pack 1 includes a battery box and one or more battery cells 4 disposed in the battery box. The battery box includes an upper box 2 and a lower box 3, the upper box 2 being able to cover the lower box 3 and form an enclosed space for the battery cells 4.

[0158] Multiple battery cells 4 can be arranged in the battery box in any way.

[0159] This application also provides an electrical device that includes the battery described above.

[0160] Furthermore, in the aforementioned electrical device, the battery can exist in the form of a single battery cell, or it can be further assembled into a battery pack.

[0161] The aforementioned battery or the battery pack assembled therefrom can be used as a power source for an electrical device or as an energy storage unit for an electrical device.

[0162] The aforementioned electrical devices may include, but are not limited to, mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc.

[0163] In some embodiments, the mobile device may be a mobile phone or a laptop computer, etc.

[0164] In some embodiments, electric vehicles include, but are not limited to: pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.

[0165] Figure 8 This is an example of an electrical device 5. This electrical device 5 can be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. To meet the high power and high energy density requirements of this electrical device 5, a battery pack can be used.

[0166] Another example of an electrical device could be a mobile phone, tablet, or laptop. These devices typically require a slim and lightweight design and can use batteries as their power source.

[0167] The present application will be described below with reference to specific embodiments, but the present application is not limited to the following embodiments. It should be understood that the appended claims summarize the scope of the present application. Under the guidance of the concept of the present application, those skilled in the art should realize that certain changes made to the various embodiments of the present application will be covered by the spirit and scope of the claims of the present application.

[0168] The following are specific examples.

[0169] Unless otherwise specified, all raw materials used in the following examples and comparative examples were obtained commercially.

[0170] Example 1

[0171] S1: Preparation of the negative electrode

[0172] ZSM-5 molecular sieve is provided: ZSM-5 zeolite has two-dimensional ten-membered ring channels, part of which are straight channels and the other part are zigzag-shaped channels. Therefore, the molecular sieve has two corresponding pore sizes D: 0.55nm and 0.56nm respectively. The silica-alumina ratio (molar ratio of silica to alumina) x=1100, the average particle size Dv50=12μm, and the specific surface area S=351m². 2 / g.

[0173] The negative electrode active material (graphite with a volume average particle size Dv50 of 12 μm), conductive agent acetylene black, binder SBR, dispersant sodium carboxymethyl cellulose CMC-Na, and the above molecular sieve were mixed and dispersed in deionized water at a mass ratio of 94:1:1:1:3 and stirred until uniformly mixed to prepare a negative electrode active slurry.

[0174] The negative electrode slurry was prepared at 7 mg / cm³. 2 The coating density is uniformly applied to the aluminum foil of the negative electrode current collector, and after drying, a negative electrode active layer is formed, resulting in a negative electrode sheet. The molecular sieve content in the obtained negative electrode active layer is 3%, and the mass ratio of molecular sieve to negative electrode active material is a1 = 0.032:1.

[0175] The physical properties of the molecular sieve in the negative electrode can be tested using the following methods:

[0176] If the negative electrode active material is a carbon-based active material, the electrode sheet is first scraped into powder, and a sample is calcined at 500℃~600℃ in an oxygen atmosphere to sinter all the binder and negative electrode active material in the electrode sheet. The remaining particles are the molecular sieve.

[0177] If the negative electrode active material is a silicon-based active material: first scrape the electrode sheet into powder, take a sample and calcine it to 500℃~600℃ in an oxygen atmosphere, then mix the sintered product with sodium hydroxide solution to react, and the filtered powder is the molecular sieve.

[0178] Structural pore size testing of molecular sieves: After separation, the molecular sieves are subjected to X-ray diffraction (XRD) testing using a Bruker D8 DISCOVER instrument. The characteristic peaks of the molecular sieves are measured and compared with the standard spectra of molecular sieves to determine the type of molecular sieve (e.g., ZSM-5). The structural pore size corresponding to this type of molecular sieve can then be determined.

[0179] The average particle size Dv50 of the separated molecular sieves was obtained by testing according to the standard GB / T19077-2016;

[0180] The specific surface area S was obtained by testing in accordance with the standard GB / T 19587-2004.

[0181] S2: Preparation of the positive electrode sheet

[0182] The nickel-cobalt-manganese ternary material NCM811, conductive agent (conductive carbon black), and binder (PVDF) were mixed in a mass ratio of 98:1:1. N-methylpyrrolidone was added, and the mixture was stirred for 6 hours to obtain a positive electrode slurry with a solid content of 50 wt%. The slurry was coated onto a positive electrode current collector aluminum foil (13 μm thick), and then dried and cold-pressed to form a positive electrode active layer with a thickness of 35 μm, thus obtaining the positive electrode sheet.

[0183] Separating membrane: A porous separating membrane is obtained by using a PE film (7μm thick).

[0184] S3: Diaphragm

[0185] S4: Preparation of electrolyte: The electrolyte is prepared by mixing the electrolyte salt LiPF6 with a mixed solvent and the additive VC (ethylene carbonate). The concentration of the electrolyte salt in the mixed solvent is 1 mol / L. The mixed solvent includes EC (ethylene carbonate), DMC (dimethyl carbonate) and EMC (ethyl methyl carbonate) in a mass ratio of 33:33:34. The mass percentage of the additive VC in the electrolyte is 2 wt%.

[0186] S5: Battery fabrication

[0187] The above-mentioned positive electrode, separator and negative electrode are wound and wrapped in an aluminum-plastic film bag. Then, the prepared electrolyte is injected, vacuum sealed and left to stand at room temperature for 6 hours to obtain the battery for subsequent testing.

[0188] S6: Performance Testing

[0189] (1) Fast charging performance test, details are as follows:

[0190] At 25°C, the battery was charged at a constant current of 0.33C to the charging cutoff voltage of 4.4V, then charged at a constant voltage to a current of 0.05C, left to stand for 5 minutes, and then discharged at a constant current of 0.33C to the discharge cutoff voltage of 2.8V. Its actual capacity was recorded as C0.

[0191] Then, the battery is sequentially charged at a constant current of 0.5C0, 1C0, 1.5C0, 2C0, 2.5C0, 3C0, 3.5C0, 4C0, 4.5C0, and 5C0 until the full battery charging cutoff voltage of 4.4V or the negative terminal cutoff potential of 0V (whichever comes first). After each charge, it is discharged at 1C0 until the full battery discharge cutoff voltage of 2.8V. The charging rate is recorded at different charging rates until 10%, 20%, 30% SOC...80% SOC. The negative electrode potential corresponding to the state of charge (SOC) is plotted at different rates. After linear fitting, the charging rate corresponding to the negative electrode potential of 0V under different SOC states is obtained. This charging rate is the charging window under that SOC state, denoted as C10%SOC, C20%SOC, C30%SOC, C40%SOC, C50%SOC, C60%SOC, C70%SOC, and C80%SOC. According to the formula: (60 / C20%SOC + 60 / C30%SOC + 60 / C40%SOC + 60 / C50%SOC + 60 / C60%SOC + 60 / C70%SOC + 60 / C80%SOC) × 10%, the charging time T of the battery from 10%SOC to 80%SOC is calculated. Please see Table 1 for details. The shorter the charging time T, the better the fast charging performance of the secondary battery.

[0192] The charging curve obtained by using the charging rate corresponding to different SOC states in the above test process as the vertical axis and SOC as the horizontal axis is as follows: Figure 9 As shown in (a), Figure 9 The vertical axis represents the charging rate (Rate, C), and the horizontal axis represents the state of charge (SOC).

[0193] (2) Charging resistance test, as detailed below:

[0194] The battery prepared above was discharged to 50% capacity at 25°C, allowed to stand for 30 minutes, and then charged for 10 seconds at a current corresponding to a 4C rate. Electrochemical impedance spectroscopy during the charging process was obtained through current impedance testing (frequency range 500kHz~30mHz, perturbation voltage 5mV). Figure 10 As shown in Figure (a), the horizontal axis represents the real part of the impedance (Z'), with units of ohms, and the vertical axis represents the imaginary part of the impedance (-Z''), with units of ohms.

[0195] (3) Fast charging cycle performance test

[0196] At 25°C, the battery prepared above was charged to 10% SOC at 0.33C, then charged to 0V at 5C according to the SOC-negative electrode potential curves at different rates in the fast charging performance test. Then it was charged to 0V at 4.5C according to the SOC-negative electrode potential curves at different rates in the fast charging performance test. Then it was charged to 0V at 4C according to the SOC-negative electrode potential curves at different rates in the fast charging performance test. This process was repeated until the battery was charged to 80% SOC. Then it was charged to 100% SOC at 0.33C, and then discharged to 0% SOC at 1C. One charge-discharge cycle is one cycle. The cycle was repeated until the battery capacity was less than 80% of the initial capacity. The number of cycles (Cy) was recorded. Please refer to Table 1 for details.

[0197] Note: In the above fast charging cycle performance test, the SOC-negative electrode potential curve used is the SOC-negative electrode potential curve of Comparative Example 1.

[0198] (4) Detection of lithium plating during cycling:

[0199] The battery that was cycled through charge and discharge in step (3) until its capacity was less than 80% of its initial capacity was fully charged, and then disassembled to observe the lithium plating on the negative electrode. The actual image of the negative electrode is shown below. Figure 11 As shown in (b), only a very small amount of lithium plating was observed.

[0200] Example 2

[0201] Example 2 is basically the same as Example 1, except that: the molecular sieve used in step S1 is ZSM-5 type molecular sieve: silicon-to-aluminum ratio x=200; in the preparation of the negative electrode sheet, the negative electrode active material (graphite), conductive agent acetylene black, binder SBR, dispersant sodium carboxymethyl cellulose CMC-Na, and the above molecular sieve are in a mass ratio of 96:1:1:1:1. The mass content of molecular sieve in the obtained negative electrode active layer is 1%, and the mass ratio of molecular sieve to negative electrode active material a1=0.01.

[0202] The other steps are the same as in Example 1. For specific parameters and results, please refer to Tables 1-3.

[0203] Example 3

[0204] Example 3 is basically the same as Example 2, except that in step S1, the negative electrode active material (graphite), conductive agent acetylene black, binder SBR, dispersant sodium carboxymethyl cellulose (CMC-Na), and the above-mentioned molecular sieve are prepared in a mass ratio of 96.7:1:1:1:0.3. The molecular sieve content in the obtained negative electrode active layer is 0.3%, and the mass ratio of molecular sieve to negative electrode active material a1 = 0.0031.

[0205] The other steps are the same as in Example 2. Please see Table 1 for specific parameters and results.

[0206] Examples 4-6

[0207] Examples 4-6 are basically the same as Example 2, except that the parameters listed in Table 1 are different. Please see Table 1 for specific values.

[0208] The other steps are the same as in Example 1. Please refer to Table 1 for specific parameters and results.

[0209] Examples 7-10

[0210] Examples 7-10 are basically the same as Example 2, except that the parameters listed in Table 1 are different. Please see Table 1 for specific values.

[0211] The other steps are the same as in Example 1. Please refer to Table 1 for specific parameters and results.

[0212] Examples 11-15

[0213] Examples 11-15 are basically the same as Example 1, except that the molecular sieve parameters listed in Table 1 are different, and in the preparation process of the negative electrode sheet, the negative electrode active material (graphite), conductive agent acetylene black, binder SBR, dispersant sodium carboxymethyl cellulose CMC-Na, and the above molecular sieve are prepared in a mass ratio of 96:1:1:1:1, the mass content of molecular sieve in the obtained negative electrode active layer is 1%, and the mass ratio of molecular sieve to negative electrode active material a1=0.01. For specific values, please refer to Table 1.

[0214] The other steps are the same as in Example 1. Please refer to Table 1 for specific parameters and results.

[0215] Comparative Example 1

[0216] Comparative Example 1 is basically the same as Example 1, except that the negative electrode is prepared in step S1 as follows:

[0217] The negative electrode active material (graphite), conductive agent acetylene black, binder SBR, and dispersant sodium carboxymethyl cellulose (CMC-Na) were mixed and dispersed in deionized water at a mass ratio of 97:1:1:1 and stirred until uniformly mixed to prepare a negative electrode active slurry.

[0218] The negative electrode slurry was prepared at 7 mg / cm³. 2 The coating density is uniformly coated on the negative electrode current collector aluminum foil, and after drying, a negative electrode active layer is formed, resulting in a negative electrode sheet.

[0219] The other steps are the same as in Example 1. For specific parameters and results, please refer to Tables 1-3.

[0220] Among them, the charging curve of the battery prepared in Comparative Example 1, obtained through fast charging performance testing, is as follows: Figure 9 As shown in (b). Comparative analysis. Figure 9 As can be seen from (a) and (b), compared with the charging curve of the battery prepared in Comparative Example 1, the fast charging capability of the battery in Example 1 is significantly improved.

[0221] The electrochemical impedance spectroscopy of the battery prepared in Comparative Example 1, obtained by charging resistance testing, is shown below. Figure 10 As shown in (b). Comparative analysis. Figure 10 As can be seen from (a) and (b), compared with the electrochemical impedance spectrum of the battery prepared in Comparative Example 1, the impedance of the battery in Example 1 is significantly reduced.

[0222] When the battery prepared in Example 1 was subjected to lithium plating cycling test, the actual image of the separated negative electrode sheet is shown below. Figure 11 As shown in (a). Comparative analysis. Figure 11 As can be seen from (a) and (b), compared with the negative electrode sheet separated from the battery prepared in Comparative Example 1, the amount of lithium plating on the surface of the negative electrode sheet separated from the battery in Example 1 is significantly less.

[0223] Comparative Example 2

[0224] Comparative Example 2 is basically the same as Example 2, except that the molecular sieve used in step S1 is different and the parameters listed in Table 1 are different. Please see Table 1 for specific values.

[0225] The other steps are the same as in Example 1. Please refer to Table 1 for specific parameters and results.

[0226] The relevant parameters and performance test results of each embodiment and comparative example are shown in Table 1. In this table, the pore size of the molecular sieve is denoted as D, the molar ratio of SiO2 to Al2O3 is denoted as x, the average particle size is denoted as Dv50, and the specific surface area is denoted as S; in the negative electrode active layer, the mass ratio of the molecular sieve to the negative electrode active material is a1, the fast charging time of the battery is denoted as T, and the number of cycles is denoted as Cy.

[0227] Table 1

[0228]

[0229] In Table 1, "\" indicates that the substance or parameter does not exist.

[0230] Analysis of the data in Table 1, and comparison of the data of Examples 1-15 with those of Comparative Examples 1-2, shows that the battery made using the negative electrode sheet of this application has reduced impedance and reduced lithium plating. This indicates that by adding a molecular sieve with a specific pore size to the negative electrode active layer, the desolvation energy barrier of metal ions during charging and discharging can be reduced, thereby reducing the probability of lithium dendrite formation and improving the fast charging performance and cycle stability of the battery.

[0231] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0232] The embodiments described above are merely illustrative of several implementation methods of this application, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of this application, and these all fall within the protection scope of this application. Therefore, the protection scope of this patent application should be determined by the appended claims, and the specification and drawings can be used to interpret the content of the claims.

Claims

1. A negative electrode sheet, characterized in that, It includes a current collector and a negative electrode active layer disposed on at least one surface of the current collector, wherein the negative electrode active layer includes a negative electrode active material and a molecular sieve in a mixed state. The pore size D of the molecular sieve satisfies: 0.3nm≤D≤2nm, and the molecular sieve includes aluminosilicate molecular sieves, wherein the molar ratio x of SiO2 and Al2O3 in the aluminosilicate molecular sieve is 50~2000.

2. The negative electrode sheet as described in claim 1, characterized in that, 0.3nm≤D≤1.5nm.

3. The negative electrode sheet as described in claim 1, characterized in that, 0.3nm≤D≤1nm.

4. The negative electrode sheet as described in claim 1, characterized in that, The silica-alumina molecular sieve includes at least one of the compounds shown in formula (1) and hydrates of the compounds shown in formula (1); zQ·Al2O3·xSiO2 (1); Q includes M + 2O and M 2+ At least one of O; Among them, M + Including H + Li + K + Na + At least one of them, M 2+ Including Ca 2+ Ba 2+ At least one of the following; 0≤z≤1.

5. The negative electrode sheet as described in claim 4, characterized in that, 50≤x≤1700。 6. The negative electrode sheet as described in claim 4, characterized in that, 100≤x≤500。 7. The negative electrode sheet as described in claim 1, characterized in that, The silica-alumina molecular sieves include at least one of potassium A-type molecular sieves, sodium A-type molecular sieves, calcium A-type molecular sieves, calcium Z-type molecular sieves, sodium Z-type molecular sieves, sodium Y-type molecular sieves, sodium mordenite zeolite molecular sieves, ZSM-5 molecular sieves, and TS-1 molecular sieves.

8. The negative electrode sheet according to any one of claims 1 to 7, characterized in that, The average particle size Dv50 of the molecular sieve satisfies: 0.1 μm <Dv50≤20μm。 9. The negative electrode sheet as described in claim 8, characterized in that, 0.3μm≤Dv50≤13μm.

10. The negative electrode sheet as described in claim 8, characterized in that, 1μm≤Dv50≤3μm.

11. The negative electrode sheet according to any one of claims 1 to 7, characterized in that, The specific surface area S of the molecular sieve satisfies: 0 <S≤1500m 2 / g.

12. The negative electrode sheet according to any one of claims 1 to 7, characterized in that, The specific surface area S of the molecular sieve satisfies: 200 m² / s² 2 / g≤S≤500m 2 / g.

13. The negative electrode sheet according to any one of claims 1 to 7, characterized in that, In the negative electrode active layer, the mass ratio of the molecular sieve to the negative electrode active material is (0.001~0.1):

1.

14. The negative electrode sheet according to any one of claims 1 to 7, characterized in that, In the negative electrode active layer, the mass ratio of the molecular sieve to the negative electrode active material is (0.005~0.03):

1.

15. A method for preparing a negative electrode, characterized in that, Includes the following steps: A negative electrode active layer is formed on at least one side of the current collector using a negative electrode active slurry; the negative electrode active slurry includes negative electrode active materials and molecular sieves in a mixed state, wherein the pore size D of the molecular sieve satisfies: 0.3nm≤D≤2nm, and the molecular sieve includes aluminosilicate molecular sieves, wherein the molar ratio x of SiO2 and Al2O3 in the aluminosilicate molecular sieve is 50~2000.

16. The method for preparing the negative electrode sheet as described in claim 15, characterized in that, The preparation steps of the negative electrode active slurry include the following steps: The negative electrode active material, the molecular sieve, and the solvent are mixed.

17. A battery, characterized in that, The battery includes a negative electrode sheet prepared by any one of claims 1 to 14 or by any one of claims 15 to 16.

18. An electrical appliance, characterized in that, The electrical device includes the battery as described in claim 17.

Citation Information

Patent Citations

  • Battery monomer, positive pole piece, negative pole piece, isolating membrane, battery and electric equipment

    CN116565364A

  • Negative plate for lithium-oxygen battery as well as preparation method and application of negative plate

    CN117438537A